Effect of content knowledge on the employment of physical education students in China - Gao, Yongqi; Geok Soh, Kim; Zakaria, Noor Syamilah; Roziah, Mohd Rasdi; Kim, Lam Soh; Wei, Guo; Hucheng, Ma (Gokmen Arslan, 2022)
Factors that affect the employment of physical education students in China include: written exams, skills interviews, course setting, teaching mode, and the knowledge required of students by the employers. Content knowledge (CK), as one of the necessary factors, has a significant impact on the employment of physical education students. The CK studied in this paper focuses on pre-service teachers (students majoring in physical education). Based on the curriculum of 26 universities and the impact of CK on the employment of physical education majors in China, 780 students were selected as samples to complete the study. The study was conducted in two stages. Firstly, the CK teaching mode was adopted on the experimental group for a 4-month periodic teaching; and then, the employment situation was clarified by tracking the students after graduation. A mathematical analysis model was thus constructed with two dimensions, preset CK, and employment. Based on the consideration of the exam content for employment of physical education students in China and the analysis of the content factors set for the examinations of physical education disciplines, it is clear that CK is not the only factor that affects employment. The perception of CK teaching mode’s influence on employment of physical education students in China is not consistent. It doesn’t involve much knowledge of sports principles. In the future, the focus should be on the development of the theoretical direction of CK in the Chinese physical education curriculum and the development of the CK teaching mode.